2010
DOI: 10.1037/a0019921
|View full text |Cite
|
Sign up to set email alerts
|

Control yourself or just eat what you like? Weight gain over a year is predicted by an interactive effect of response inhibition and implicit preference for snack foods.

Abstract: The results strongly confirmed our expectations: participants with strong implicit preferences for snack foods and low inhibitory capacity gained the most weight. These findings imply that ineffective response inhibition may render people vulnerable to excessive or impulsive behavior in general, but that the manifestation thereof is determined by domain-specific preferences or needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
297
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(322 citation statements)
references
References 35 publications
20
297
2
3
Order By: Relevance
“…Once again, we found that the two groups differed in their automatic hunger responses to healthy and unhealthy foods, and that of healthy (e.g., fruit) and unhealthy (e.g., candy) foods predict whether people will purchase or consume the former over the latter (Ellis, Kiviniemi, & Cook-Cottone, 2014;Prestwich, Hurling & Baker, 2011) as well as their likelihood of gaining weight across a one year period (Nederkoorn et al, 2010). Despite such findings, no published study has examined whether automatic food-related responses represent a useful determinant of food intake in clinical populations.…”
Section: Discussionmentioning
confidence: 67%
“…Once again, we found that the two groups differed in their automatic hunger responses to healthy and unhealthy foods, and that of healthy (e.g., fruit) and unhealthy (e.g., candy) foods predict whether people will purchase or consume the former over the latter (Ellis, Kiviniemi, & Cook-Cottone, 2014;Prestwich, Hurling & Baker, 2011) as well as their likelihood of gaining weight across a one year period (Nederkoorn et al, 2010). Despite such findings, no published study has examined whether automatic food-related responses represent a useful determinant of food intake in clinical populations.…”
Section: Discussionmentioning
confidence: 67%
“…This resulted in 30 presentations of food words in each block; 30 presentations of negative words and 12 presentations of positive words in the food + positive block; and 30 presentations of positive words and 12 presentations of negative words in the food + negative block (Nederkoorn et al, 2010;Olson & Fazio, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…As used in previous research, the target category was labelled "food", and the positive and negative evaluative categories were labelled "I like", and "I dislike", respectively (Craeynest, Crombez, Haerens, & De Bourdeaudhuij, 2007;Houben & Wiers, 2007;Nederkoorn et al, 2010;Olson & Fazio, 2004). The target words included six unhealthy food words: chocolate, cake, ice-cream, chips, pizza, and hamburger and are similar to those used in previous studies (e.g., Fishbach, Zhang, & Trope, 2010;Richetin et al, 2007;Roefs, Herman, MacLeod, Smulders, & Jansen, 2005;Roefs & Jansen, 2002;Roefs et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such control is impaired under certain conditions in both psychologically/neurologically typical individuals [e.g., overeating during stressful periods (2)] and those with pathological conditions [e.g., addiction (3)]. Consequently, understanding the neural circuitry supporting inhibitory aspects of cognitive control has the potential to provide key insights into a wide array of difficulties, ranging from common activities of daily life to psychiatric disorders.…”
mentioning
confidence: 99%